Influence of spacing on the initial production of hedgerow ‘Arbequina’ olive orchards - León, L.; de la Rosa, R.; Rallo, L.; Guerrero, N.; Barranco, D. (Spanish Journal of Agricultural Research, 2007)
A new type of olive (Olea europaea L.) orchard, based on high-density hedgerows harvested by vineyard type straddleharvesters has appeared in recent years. This system greatly simplifies olive harvesting, which has a high labour demand in standard olive orchards. There are, however, no specific low-vigour olive cultivars or dwarfing rootstocks adapted to this system, as exist in other fruit crops. It is therefore crucial to select the optimum density for maximum production without causing serious competition problems. In this study we present initial results of the effect of densities, ranging from 780 to 2,580 olive trees ha-1, on the production of an ‘Arbequina’ olive hedgerow orchard during the first seven years after planting. There were no significant differences in fruit characteristics (oil content and moisture) among density treatments. Density had a linear negative influence on fruit yield tree-1. In contrast, accumulated yield ha-1, for both fruit and oil yield, showed a linear increase with increased density, with coefficients of determination ranging from 0.37 to 0.72. Accumulated oil yield at high density was up to 5,000 kg ha-1 more than at the low density